An illustrated textbook, ear, nose & throat, and head and neck surgery - Shrivastav, Rakesh Prasad (Jaypee Brothers Medical Pub., 2014)
Second edition presenting latest advances in ENT and head and neck surgery. Covers many new topics and summarises key points for each chapter. Previous edition published in 2008.